VD_FINDINFO Décision / 2010 / 67 vom 16. April 2010 - VD Tribunal cantonal (2010)
RADIATION DU RÔLE, RETRAITVOIE DE DROIT | 1 al. 1 LAMal, 56 al. 2 LPGA, 56 LPGA, 57 LPGA, 58 LPGA, 59 LPGA, 61 let. a LPGA, 61 let. g LPGA, 94 al. 1 let. c LPA-VD